Metodologi Pemikiran Hukum Islam Fazlur Rahman - Ma'adul Yaqien Makkarateng (Al-Bayyinah, 2019)
This study aims to examine the methodology of Fazlur Rahman's on Islamic law which can be the answer to the renewal of Islamic thought. This study is a descriptive-qualitative study that applies a historical and philosophical approach. Every data is collected through the library research by collecting research materials from various literature. The result of the analysis reveals that Fazlur Rahman’s thought is to set out the Tatbiq approach as a systematic way toward Alquran and al-Hadith and ultimately purchased three kinds of method which are The Critical History Method, The Systematic Interpretation Method and a Double Movement Method. Keywords: Islamic Law-Methodology-Fazlur Rahman.